If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(m + -5) + 6 = 0 Reorder the terms: 2(-5 + m) + 6 = 0 (-5 * 2 + m * 2) + 6 = 0 (-10 + 2m) + 6 = 0 Reorder the terms: -10 + 6 + 2m = 0 Combine like terms: -10 + 6 = -4 -4 + 2m = 0 Solving -4 + 2m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 2m = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 2m = 0 + 4 2m = 0 + 4 Combine like terms: 0 + 4 = 4 2m = 4 Divide each side by '2'. m = 2 Simplifying m = 2
| 1-5x=10-2x | | -6=3(u+-3) | | 15x+6=2x-3 | | 3x+7=6x+7 | | 4(n-3)-2(-3+n)= | | -3(-5u+6)-3u=4(u-6)-8 | | 10+4y= | | 8(4x-1)-12x=(2x-6) | | n(2)+14=98 | | n(2)14=98 | | -1/2x+3(0)=-3 | | 2log(2x)=1 | | -6=3-m | | 125n^2-45=0 | | 0.04x+0.03(x-20)=1.25 | | 6x-61=-3x+65 | | 4(w+1)+4=20 | | 5x-3=6x-7 | | -3e+2=5e-4 | | 3-.75x=8 | | 8b^2+10b+3=0 | | 7x-10=-2-x | | f(25)+f(26)= | | -150+9x=122-8x | | 3(r-8)-(-4)=7 | | 6-4x=5x-12 | | 2(c+3)=-9 | | 4r^3+11r^2-3r=0 | | 2(m-7)=4 | | -47-11x=-3x+73 | | 8x+3+2x+17=180 | | 14x-32=24 |